DETERMINANTS OF ACCESS TO HEALTH EDUCATION IN EXTENSION SERVICE AND IMPLICATION FOR NUTRITION TRANSITION AMONG POULTRY FARMERS IN LAGOS STATE, NIGERIA - Awoyinka, R.I.; Babalola, D.A.; Akintunde, O.A.; Esosa, O.R.; Aminu, O.O.; Akinbile, L.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the determinants of access to health education among poultry farmers in Lagos State, Nigeria, and its implications for nutrition transition. A structured questionnaire was used to collect data from 93 poultry farmers, focusing on their socio-economic characteristics, level of access to health education, and dietary habits. The findings revealed that the majority (80.6%) of poultry farmers were male, with a significant proportion (67.7%) aged above 50 years, indicating an aging farming population. Majority (77.4%) of the respondents attended tertiary education, which suggests a high potential for knowledge assimilation and implementation of best practices. Despite this, access to health education on crucial topics such as family planning (75.3%), food hygiene protocols (59.1%), pathogenic and cardiovascular diseases (59.1%), and animal health (55.9%) was predominantly poor. These gaps in health education may affect the farmers’ health outcomes and overall productivity. Additionally, findings indicated a high reliance on staple food consumption (87.9%), which raises concerns regarding dietary diversity and nutrition transition. The study shows the need for targeted interventions to improve health education outreach in extension services, promote better nutritional awareness, and enhance overall farm productivity. Strengthening extension services with tailored health education programs can mitigate health risks and foster a more resilient poultry farming sector in Lagos State.